2020
DOI: 10.1177/2377960820930153
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Standardized Patients on First Semester Nursing Students Self-Confidence, Satisfaction, and Communication in a Simulated Clinical Case

Abstract: Background Utilizing standardized patients (SPs) as a strategy to potentially improve beginning level nursing students’ confidence, satisfaction, and communication after simulated clinical cases is an innovative approach in nursing education. Aim The aim of this study was to examine to what extent an SP affected first semester nursing students’ self-confidence, satisfaction, and communication using a simulated clinical case. Methods First semester undergraduate students in a bachelors of nursing program at a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…Thus, they suggested that mixed-method studies with larger samples, valid tools, and rigorous qualitative protocols would be required to guarantee adequate triangulation of research results. Our students reported high satisfaction scores for the simulation program, similar to those in other programs that trained communication skills with standardized patients (Donovan and Mullen, 2019;Goh et al, 2016;Hsu et al, 2015;Jang et al, 2019;Johnson et al, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Thus, they suggested that mixed-method studies with larger samples, valid tools, and rigorous qualitative protocols would be required to guarantee adequate triangulation of research results. Our students reported high satisfaction scores for the simulation program, similar to those in other programs that trained communication skills with standardized patients (Donovan and Mullen, 2019;Goh et al, 2016;Hsu et al, 2015;Jang et al, 2019;Johnson et al, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…An SP in simulation training provides valuable feedback on the patient's perspective and contributes to the achievement of learning goals ( Johnson et al, 2020 ; MacLean et al, 2017 ; Söderberg et al, 2017 ; Vandyk et al, 2018 ). Dalwood et al (2020) found no significant differences between students who simulated with peers as patients and students who simulated with trained persons as patients.…”
Section: Review Of Literaturementioning
confidence: 99%
“…It offers the opportunity to structure and practice clinical experiences in a controlled and safe environment (Hall & Tori, 2017). Standardized patients (SPs) have been used for many years to create simulated cases that are designed to create a high level of realism in nursing and medical education programs (Johnson et al, 2020). SPs are people who are trained to perform and represent patient's conditions (e.g., symptoms or social situations); they may also provide informative feedback.…”
Section: Introductionmentioning
confidence: 99%